2010
DOI: 10.1002/ijc.25119
|View full text |Cite
|
Sign up to set email alerts
|

Isoalvaxanthone inhibits colon cancer cell proliferation, migration and invasion through inactivating Rac1 and AP‐1

Abstract: Isoalvaxanthone (IAX) is a bioactive xanthone isolated from Cudrania cochinchinensis (Lour.). However, the function and mechanism of this compound in cancer migration and invasion have not been elucidated to date. In this study, we found that IAX could suppress various steps of tumor metastasis including proliferation, migration and invasion in a dose-dependent manner on colorectal cancer cells. Especially matrix metalloproteinase 2 (MMP-2), the pivotal factor in cancer invasion, was suppressed both on activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…roots remarkably suppressed the multistep of metastatic process of B16F10 cells proliferation, adhesion, invasion and migration at the non-toxic effective doses, indicating that the presence of these active xanthones may be in part responsible for their effects on cell proliferation and metastasis capability of this metastatic cells. Our observations correlate with the earlier reports that two main xanthones of isoalvaxanthone isolated from Cudrania cochinchinensis (Lour) and cudratricusxanthone G, isolated from Cudrania tricuspidata exerted anti-metastatic action in human colorectal carcinoma (SW620) cells by targeting MMP-2 through regulating the activities of Rac 1, Cdc 42, and their downstream transcriptional factor AP-1 (Wang et al, 2010;Kuang et al, 2011). Further studies have to find out the exact molecular mechanism of actions of the active xanthones and other isolated compounds in inhibiting the cascade of events of metastasis.…”
Section: Ma-2supporting
confidence: 92%
See 1 more Smart Citation
“…roots remarkably suppressed the multistep of metastatic process of B16F10 cells proliferation, adhesion, invasion and migration at the non-toxic effective doses, indicating that the presence of these active xanthones may be in part responsible for their effects on cell proliferation and metastasis capability of this metastatic cells. Our observations correlate with the earlier reports that two main xanthones of isoalvaxanthone isolated from Cudrania cochinchinensis (Lour) and cudratricusxanthone G, isolated from Cudrania tricuspidata exerted anti-metastatic action in human colorectal carcinoma (SW620) cells by targeting MMP-2 through regulating the activities of Rac 1, Cdc 42, and their downstream transcriptional factor AP-1 (Wang et al, 2010;Kuang et al, 2011). Further studies have to find out the exact molecular mechanism of actions of the active xanthones and other isolated compounds in inhibiting the cascade of events of metastasis.…”
Section: Ma-2supporting
confidence: 92%
“…were found to possess antiinflammatory (Chang et al, 2008), anti-lipid peroxidative (Chang et al, 1994), antioxidative Lee et al, 2006;Jeong et al, 2009Jeong et al, : 2012, hepatoprotective , antibacterial (Fukai et al, 2004), antifungal , antitumor effects and cytotoxicity against various cancer cells (Seo, et al, 2001;Zou et al, 2004;Wang et al, 2005Wang et al, : 2010Kuang et al, 2011). More extensive phytochemical and pharmacological studies, several xanthones and flavonoids as the main active components have been identified from this genus and some of them have been reported to possess significant pharmacological properties, including anti-inflammatory (Lin et al, 2012), anti-cancer Wang et al, 2010;Kuang et al, 2011), antibacterial (Fukai, et al, 2004) and anti-HIV (Groweiss et al, 2000) activities. For instance, macluraxanthone B and C isolated from Maclura tinctoria exhibited anti-HIV activity (Groweiss et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It appears that either hydrophobic or H-bonding interactions would lead to a tighter contact with the enzyme binding site, features that, when combined, would lead to a further substantial increase of the binding potency. Comparing 14 and 15 with 16 strongly suggests the prevalence of 1,5-di-substitution (16), at the peri-positions, over their mono-substituted variants (14,15). This is supported by the clustering caused during docking where the iodine in 14 and 15 is placed in a very hydrophobic region, whereas in analogue 16, steric constraint forces iodine atoms into less hydrophobic positions.…”
Section: Interaction Of Hgsta1-1 With the Xanthone Derivativesmentioning
confidence: 90%
“…Glutamate supplementation [22], red grape skin polyphenolic extract [23], acacetin (a flavone found in honey and other sources) [24], isoalvaxanthone (a polyphenolic xanthone, which is biosynthetically related to flavonoids found in Cudrania cochinchinensis, Lour. and used in Chinese fold medicine) [25], and genistein (an isoflavone found in soy products) [26] inhibit p38 and/or its phosphorylation. Natural compounds that increase p38 and/or p38 phosphorylation in various cancer cell types include the following: glutamine, tyrosine and phenylalanine, and methionine restriction [27], lupulone (a prenylated flavonoid found in hops used in the manufacture of beer) [28], celastrol (a quinone methide triterpene extracted from the root bark of Tripterygium wilfordii, which in Chinese medicine is known as Thunder of God Vine) [29], berberine (an isoquinoline alkaloid with medicinal properties widely distributed in plants, notably Oregon grape, Mahonia aquifolium) [30], quercetin (a flavonol found in fruits, vegetables, leaves and grains) [31], and β-caryophyllene (a bicyclic sessquiterpene found in many essential oils, rosemary, hops, and black pepper) [32].…”
Section: Glucosinolatesmentioning
confidence: 99%